Gospodarka społeczna a sytuacja współczesnej młodzieży. Zarys koncepcji = Social economy and the situation of contemporary youth. Outline of the concept - Kwiatkowski, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper concerns both research and practical issues. Its aim is to present a new outlook on the economy functions and social entrepreneurship. The novelty in the demonstrated approach lies in the attempt to link the indicated issue with the problem of the situation of contemporary youth.
Keywords: ekonomia społeczna; młodzież; aktywność społeczna; aktywność zawodowa